Pocketbook on Prophet Hadith to Prevent Bullying Behaviour - Billah, A.A.M; Wantini; Suyatno (LETIGES, 2024)
The increasing cases of bullying and various forms of violence in Islamic boarding schools have encouraged researchers to develop a Pocketbook containing the Prophet's Hadith which aims to guide students in understanding moral teachings that can prevent violent behavior. This study aims to produce a Pocketbook of the Prophet's Hadith that can be integrated into the Islamic boarding school curriculum to prevent bullying. This media is expected to be a source of inspiration and understanding for students about the importance of avoiding bullying behavior. Research methods are in the form of development research or R&D. The development model used is the 10-step method by Sugiyono. The product's effectiveness is tested by comparing the pre and Post-test values. This study uses data collection techniques through observation, questionnaires, documentation, and interviews. In terms of student response data analysis, evaluation is conducted using the Guttman scale, which includes only two possible answers: